DIFFICULTIES OF NON-PHILOLOGICAL STUDENTS IN LEARNING VOCABULARY AND USING RELEVANT TEXTS IN TEACHING ENGLISH - Dadabayev Zafar; Olimov Sardor (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
A comprehensive solution to the practical, educational, educational and developing tasks of learning is possible only when it affects not only the consciousness of students but also penetration into their emotional sphere. It is very important to teach foreign language in higher education institutions that do not specialize in languages, because a foreign language plays an important role in preparing students for full development. It requires them to further develop their skills and abilities, to combine education and upbringing.